Depletion of protein kinase Cepsilon in normal and scleroderma lung fibroblasts has opposite effects on tenascin expression - Tourkina, E; Hoffman, S; Fenton, 2nd, J W; Lipsitz, S; Silver, R M; Ludwicka-Bradley, A (Arthritis and rheumatism, 2001)
To determine whether the extracellular matrix protein tenascin-C (TN-C) is overexpressed in lung fibroblasts from systemic sclerosis (SSc) patients, the molecular mechanisms regulating TN-C secretion in SSc and normal lung fibroblasts, and how these processes might contribute to lung fibrosis in SSc patients. TN-C secretion by SSc and normal fibroblasts was compared in vivo (in bronchoalveolar lavage [BAL] fluid) and in vitro (in culture medium). The ability of thrombin to induce TN-C was confirmed at both the protein and the messenger RNA (mRNA) level. The role of protein kinase Cepsilon (PKCepsilon) in the expression of TN-C was evaluated by determining the effects of thrombin on PKCepsilon levels and by directly manipulating PKCepsilon levels via the use of antisense oligonucleotides. BAL fluid from SSc patients contained high levels of TN-C, whereas that from normal subjects contained little or no TN-C. In vitro, SSc lung fibroblasts expressed much higher amounts of TN-C than did normal lung fibroblasts. Consistent with the idea that thrombin is a physiologic inducer of TN-C, thrombin stimulated TN-C mRNA and protein expression in both SSc and normal lung fibroblasts by a mechanism that required proteolytic cleavage of the thrombin receptor. Surprisingly, thrombin treatment and antisense oligonucleotide-mediated depletion of PKCepsilon indicated that TN-C expression is regulated via opposite signaling mechanisms in SSc and normal cells. In SSc lung fibroblasts, thrombin decreased PKCepsilon levels, and the decreased PKCepsilon induced TN-C secretion; in normal fibroblasts, thrombin increased PKCepsilon levels, and the increased PKCepsilon induced TN-C secretion. Normal and SSc lung fibroblasts also differed in the subcellular localization of PKCepsilon, both before and after thrombin treatment. These studies are the first to demonstrate that thrombin is a potent simulator of TN-C in lung fibroblasts and that PKCepsilon is a critical regulator of TN-C protein levels in these cells. Furthermore, our results indicate that both the regulation of PKCepsilon levels by thrombin and the regulation of TN-C levels by PKCepsilon are defective in SSc lung fibroblasts.